Cochrane Database of Systematic Reviews 2010
DOI: 10.1002/14651858.cd007354.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Benzodiazepines for the relief of breathlessness in advanced malignant and non-malignant diseases in adults

Abstract: There is no evidence for a beneficial effect of benzodiazepines for the relief of breathlessness in patients with advanced cancer and COPD. There is a slight but non-significant trend towards a beneficial effect but the overall effect size is small. Benzodiazepines caused more drowsiness as an adverse effect compared to placebo, but less compared to morphine. These results justify considering benzodiazepines as a second or third-line treatment within an individual therapeutic trial, when opioids and non-pharma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
100
2
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(114 citation statements)
references
References 82 publications
5
100
2
7
Order By: Relevance
“…A number of other pharmacologic agents, including anxiolytics (251)(252)(253), antidepressants (254), phenothiazines (237,255), indomethacin (256,257), inhaled topical anesthetics (258,259), nitrous oxide (260), and sodium bicarbonate (261), have been found to be ineffective or lack sufficient data to recommend their use (247).…”
Section: Treatmentmentioning
confidence: 99%
“…A number of other pharmacologic agents, including anxiolytics (251)(252)(253), antidepressants (254), phenothiazines (237,255), indomethacin (256,257), inhaled topical anesthetics (258,259), nitrous oxide (260), and sodium bicarbonate (261), have been found to be ineffective or lack sufficient data to recommend their use (247).…”
Section: Treatmentmentioning
confidence: 99%
“…They found that the combination of this benzodiazepine with morphine had a positive effect on dyspnea with minimal effect on somnolence. [11] In contrast to these results, Simon and et al (2010) stated that there is no evidence to support the efficacy of benzodiazepines in the palliation of dyspnea in their metaanalysis. [5,12] More randomized, controlled studies aimed at assessing the efficacy of benzodiazepines used in conjunction with other opioids need to be performed.…”
Section: Diagnosis Of Dyspneamentioning
confidence: 95%
“…The authors did not find any evidence for or against the effectiveness of benzodiazepines (in any formulation) in treating breathlessness. 15 Benzodiazepines caused more side effects than placebo (especially drowsiness or somnolence), but fewer than opioids. 15 A subsequent review of non-opioid therapies in chronic breathlessness also found insufficient evidence to support benzodiazepine use.…”
Section: Benzodiazepinesmentioning
confidence: 99%